The Potential Of Nickel Slag with Humic Substance Addition as Ameliorating Materials on Gajrug Red-Yellow Podzolic - Febrianti Rosalina; Dyah Tjahyandari; Darmawan Darmawan (Universitas Sebelas Maret, 2018)
Nickel slag and humic substance have a strong potential for use as soil ameliorants in land remediation, owing to their chemical properties that can improve acidic soils. This study aimed to determine their effect on red-yellow podzolic soil. This greenhouse incubation study used a 2-factorial completely randomized design. Factor 1 was nickel slag at 4levels (0, 8, 12, and 16 ton ha-1), while Factor 2 was humic substance at 3 levels (0, 15, and 30 litre ha-1), with 3 replications. Statistical analysis of the data used analysis of variance, and whenever a significant difference was detected, further verification was tested using Duncan’s Multiple Range Test at a level of significance (α) of 5%. The results showed that the application of nickel slag and humic substance can increase the values of pH, total-N, available-P, and exchangeable-Mg of the red-yellow podzolic soil, but also decreased exchangeable-H. The interactive effects of nickel slag and humic substance can raise soil K-exchangeable only. The levels of heavy metals (Pb, Cd and As) in the soil after the application of nickel slag and humic substance remain within normal limits that is, they are environmentally safe for use as a soil ameliorant